Nonlinearities Distribution Homotopy Perturbation Method Applied to Solve Nonlinear Problems: Thomas-Fermi Equation as a Case Study. (20th January 2015) - Filobello-Nino, U.; Vazquez-Leal, H.; Boubaker, K.; Sarmiento-Reyes, A.; Perez-Sesma, A.; Diaz-Sanchez, A.; Jimenez-Fernandez, V. M.; Cervantes-Perez, J.; Sanchez-Orea, J.; Huerta-Chua, J.; Morales-Mendoza, L. J.; Gonzalez-Lee, M.; et al.
Abstract : We propose an approximate solution of T-F equation, obtained by using the nonlinearities distribution homotopy perturbation method (NDHPM). Besides, we show a table of comparison, between this proposed approximate solution and a numerical of T-F, by establishing the accuracy of the results.